Inter-relations of brain neurosteroids and monoamines towards reproduction in fish - A Kalarani; V Vinodha; Inbaraj R Moses (Reproduction and Breeding, 2021)
Reproduction is the physiological process which results in the sustainability of the species and brain has been the commanding organ of reproduction. In general, reproduction is governed by hypothalamic-pituitary-gonadal (HPG) axis. As a primary factor in the axis, gonadotrophin releasing hormone (GnRH) from hypothalamus acts on pituitary to control the release of gonadotropins which in turn regulate gonadal activity. Neurotransmitters such as monoamine, amino acids, neurosteroids and peptides are involved in the neuroendocrine control of reproduction. Neurosteroids are actively involved in governing the sexual behaviour, sexual differentiation, and brain sexual dimorphism while neuroamines are the potential neurotransmitter in modulating the reproduction and its related behaviours. To be specific estrogen and progesterone have a control on GnRH secretion. Similarly, dopamine (DA) and serotonin (5-HT), the monoamies have access to GnRH release in brain. Their overlapping functional role and coexistence in brain leads to an inquisitive thinking over their functional integration towards reproduction. This review highlights the synthesis, location and their functional role in governing the reproduction and an attempt to understand the interrelationship between them during maturation and reproduction. It aims in laying out a map of how the neuroamines and neurosteroids interacts in brain during reproduction.